The Effect of Fatigue on Changing the Curve of Shooting Accuracy for Soccer Players' in Palestine - Jamal Abubshara (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This paper aims to explore the effect of acutely induced fatigue on the curve of change in shooting accuracy among Palestine soccer players. To achieve the study goal, the experimental approach was used by designing one-group  with pre and post- measurements applied to a sample of (10) elite male soccer players in the 2018/2019 sports season. The repeated measurements were applied by six (6) measurements before, between and after implementing an intensive and intermittent exercise protocol. To process the data, the researcher used Pearson correlation and repeated measures of ANOVA. The study's results showed that there is a negative effect of the fatigue protocol on shooting accuracy, through the presence of statistically significant differences (α≤ 0.05) in the shooting accuracy in the first measurement mean and the mean of the measurements (second, third, fourth, fifth, sixth), in favor of the first measurement mean. Based on the study results, the researcher recommends that the coaches should have trained players to shoot under the influence of fatigue; in addition, coaches should predict the periods of fatigue for each player inorder to develop strategic plans for the game.